Identification of antibacterial peptides from Maillard reaction products of half-fin anchovy hydrolysates/glucose via LC-ESI-QTOF-MS analysis. (September 2017) - Song, Ru; Shi, Qingqing; Yang, Peiyu; Wei, Rongbian
Highlights: Short peptides were identified from the MRPs of half-fin anchovy hydrolysates and glucose. All identified peptides had positively charged R residues at the N- or C-terminus. Secondary structures of the identified peptides were predicted and evaluated. Peptide WLPVVR demonstrated the highest inhibition rate than other synthetic peptides. All active peptides had the capacity to cluster and decompose liposomes. Abstract: We aimed to identify antibacterial peptides from Maillard reaction products of half-fin anchovy hydrolysates/glucose. Seven peptides from the active fraction of P3-2 derived from DEAE-Sepharose™ CL-6B chromatography and PL aquagel-OH 30 on HPLC system were identified by liquid chromatography-electrospray ionization/multi-stage mass spectrometry, and five peptides were selected for further synthesis on the basis of peptide sequences. The anionic peptide FFTQATDLLSR adopted an α-helical structure, as predicted by Network Protein Sequence @ analysis and helical wheel projection, and further determined using circular dichroism assay. The cationic peptide WLPVVR exhibited stronger inhibition effects against Escherichia coli than other peptides at similar concentration. Furthermore, differential sizes of hydrodynamic diameters of anionic 1, 2-dimyristoyl-sn-glycero-3-phosphocholine liposome vesicles treated with peptides were observed, suggesting the clustering and decomposition of peptide on liposome vesicles. To the best of our knowledge, this is the first study that reports antibacterial peptides derived from the MRPs of half-fin anchovy hydrolysates.